Governance in Samarinda City Using TOGAF (The Open Group Architecture Framework): Literature Review - Rizki Galang Rahmadani; Oky Dwi Nurhayati; Dinar Mutiara Kusumo Nugraheni (Green Publisher, 2025)
Effective governance is essential for ensuring the efficient delivery of public services and fostering community development. In Samarinda City, addressing administrative and developmental challenges requires the implementation of a robust governance framework. This research explores the application of TOGAF (The Open Group Architecture Framework) to improve the efficiency and effectiveness of local governance in Samarinda City. The study aims to analyze how TOGAF can strengthen strategic alignment, decision-making, and operational efficiency within local government frameworks. This research employs a qualitative approach through a literature review of academic articles, case studies, and industry reports on the application of TOGAF in governance contexts. The findings indicate that TOGAF facilitates strategic alignment of IT resources with governance goals, improves decision-making through structured methodologies, enhances operational efficiency through resource optimization, and promotes interoperability between government departments. However, challenges such as the framework's complexity, resource demands, and adaptability to local contexts must be addressed. The results suggest that adopting TOGAF incrementally, investing in capacity building, and ensuring stakeholder engagement are crucial for successful implementation. These findings have important implications for the Samarinda City Government, providing practical recommendations to enhance governance through TOGAF, and contributing to the broader literature on IT frameworks in public sector governance. Further research could explore case studies of TOGAF implementation in other cities with similar challenges to offer additional insights into its practical applications.